The risk of preterm labor after COVID-19 vaccination before and during pregnancy - de Feijter, M.; Vissers, L. C. M.; Davidson, L.; Kant, A. C.; Woestenberg, P. J. (Frontiers in Drug Safety and Regulation, 2023)
Background: Pregnant women have a higher risk of severe illness and adverse pregnancy outcomes due to a SARS-CoV-2 infection. COVID-19 vaccination can prevent (severe) infection. Observational studies are needed to ascertain safety of COVID-19 vaccination during pregnancy.Aim: Estimate whether COVID-19 vaccination during pregnancy is associated with the risk of preterm labor (PL).In this prospective cohort study, we included 5,910 pregnant women (mean age: 33.0±3.7 years) who entered the Dutch Pregnancy Drug Register between February 2021 and August 2022.Information on COVID-19 vaccinations, PL, and confounders were self-reported using web-based questionnaires. The hazard ratio (HR) on PL, comparing those who received ≥1 COVID-19 vaccine during any moment of pregnancy to those who did not, was estimated using survival analyses with vaccination as time-varying exposure. Additionally, we estimated the risk of PL after COVID-19 vaccination prior to pregnancy, and after COVID-19 vaccination during trimester 1, 2, or 3 of pregnancy.Findings: A total of 5,227 (88%) participants received ≥1 COVID-19 vaccine between gestational week 2 and 37. We observed no statistically significant association of COVID-19 vaccination during pregnancy (adjusted HR=0.93, 95%CI=0.59;1.45) nor of COVID-19 vaccination prior to pregnancy (adjusted HR=1.09, 95%CI=0.70;1.71) with the risk of PL. Moreover, we observed no association between the risk of PL and COVID-19 vaccination in any trimester of pregnancy.Discussion: We demonstrated that COVID-19 vaccination prior to or during pregnancy is not associated with an increased risk of PL.Conclusions: These results add to the growing evidence supporting safety of COVID-19 vaccination during pregnancy.